Pharmacokinetic Study of Perioperative Intravenous Ifosfamide. (21st September 2011) - Van der Speeten, Kurt; Stuart, O. Anthony; Mahteme, Haile; Sugarbaker, Paul H.
Abstract : The use of cancer chemotherapy and hyperthermia as part of a surgical procedure in the management of patients with peritoneal carcinomatosis has gained prominence in recent years with selected patients showing benefit. Patients with peritoneal surface malignancy following cancer resection were treated with intraperitoneal hyperthermic (41.5–42.5°C) cisplatin and doxorubicin combined with the infusion of systemic ifosfamide chemotherapy. The concentrations of ifosfamide and 4-hydroxyifosfamide were determined in plasma, peritoneal fluid, urine, and when possible, within small tumor nodules less than 1 cm. Plasma concentrations of ifosfamide exceeded peritoneal fluid levels of ifosfamide during the 90 minutes of chemotherapy infusion. Both ifosfamide and 4-hydroxyifosfamide could be recovered from peritoneal tumor nodules throughout the 90 minutes of ifosfamide continuous infusion and exceeded plasma concentrations. 4-Hydroxyifosfamide within peritoneal surface cancer nodules suggested a favorable pharmacologic endpoint in the study of ifosfamide administered in the operating room.